2020
DOI: 10.51791/njap.v47i1.235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of method of preservation on the chemical composition of Enterolobium cyclocarpum leaves

Abstract: Enterolobium cyclocarpum leaves are less acceptable by ruminants due to their high contents of anti-nutritional factors. The effect of preserving Enterolobium cyclocarpum leaves as hay and silage or silage: hay combinations on the proximate, fibre fractions, anti-nutritional factors, minerals and vitamins compositions were investigated in this study. Six experimental treatments consisting of 100% fresh Enterolobium cyclocarpum leaves, 100% ensiled Enterolobium cyclocarpum leaves, 100% sun dried Enterolobium cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
2
2
Order By: Relevance
“…Tannin contents were lowest (13.73 mg/100g) in the control diet and increased (24.02, 28.93 and 29.71 mg/100g) significantly (p<0.05) in diets 2, 3 and 4, respectively with increased EC leaves in the diet. Tannic contents obtained in this study were higher than the range of 3.11 to 10.31 mg/100g reported by Bassey et al (2014) for Rauvolfia vomitoria>Palisota hirsute>Manniophytonfulvum>Spondiasmombin but lower than the 93.40 mg/100g reported by Ekanem et al (2020b) for fresh EC leaves. High contents of tannin obtained in this study corroborates the high concentration (+++) of tannins reported by Galindo et al (2014) for Enterolobium cyclocarpum leaves.…”
Section: Chemical Composition Of the Experimental Dietscontrasting
confidence: 84%
See 3 more Smart Citations
“…Tannin contents were lowest (13.73 mg/100g) in the control diet and increased (24.02, 28.93 and 29.71 mg/100g) significantly (p<0.05) in diets 2, 3 and 4, respectively with increased EC leaves in the diet. Tannic contents obtained in this study were higher than the range of 3.11 to 10.31 mg/100g reported by Bassey et al (2014) for Rauvolfia vomitoria>Palisota hirsute>Manniophytonfulvum>Spondiasmombin but lower than the 93.40 mg/100g reported by Ekanem et al (2020b) for fresh EC leaves. High contents of tannin obtained in this study corroborates the high concentration (+++) of tannins reported by Galindo et al (2014) for Enterolobium cyclocarpum leaves.…”
Section: Chemical Composition Of the Experimental Dietscontrasting
confidence: 84%
“…Values for oxalate obtained in this study were lower than the range of 202.40 to 598.40 mg/100 reported for Rauvolfia vomitoria>Palisota hirsute>Manniophyton fulvum>Spondias mombin found in Akwa Ibom State. Similarly, concentration of oxalic acid in the diet were lower than the value of 450.21 mg/100g reported by Ekanem et al (2020b) for fresh EC leaves. Phytic acid concentration obtained in this study ranged from 6.60 to 7.49 mg/100g.…”
Section: Chemical Composition Of the Experimental Dietscontrasting
confidence: 62%
See 2 more Smart Citations